Umberto D. - Zavattini, Cesare 1902-1989; Cicognini, Alessandro 1906-1995 (<<The>> Criterion Collection, 2011)
"This neorealist masterpiece by Vittorio De Sica follows an elderly pensioner as he strives to make ends meet during Italy’s postwar economic recovery. Alone except for his dog, Flike, Umberto struggles to maintain his dignity in a city where human kindness seems to have been swallowed up by the forces of modernization. His simple quest to satisfy his basic needs—food, shelter, companionship—makes for one of the most heartbreaking stories ever filmed, and an essential classic of world cinema." [criterion.com]
Original: Italien 1952
Blu-ray special edition features: high-definition digital restoration, with uncompressed monaural soundtrack ; "That’s life: Vittorio De Sica", a fifty-five-minute documentary about the director’s career, made for Italian television in 2001 ; interview with actress Maria Pia Casilio from 2003 ; trailer ; plus: A booklet featuring an essay by critic Stuart Klawans and reprinted recollections by De Sica and actor Carlo Battisti
Bildformat 1.37:1
Keywords: Film; Blu-Ray-Disc